Improving member loyalty through service quality: A case study of Citra Abadi Savings and Loan Cooperative - Rahayu, Nanda; Manafe, Leonard Adrie; Nugroho, Dodit Cahyo (Priviet Social Sciences Journal, 2025)
This study aims to analyze the effect of service quality on member satisfaction at the Citra Abadi Savings and Loan Cooperative (KSP). Service quality was assessed using five main elements: tangibles (physical evidence), Reliability, Responsiveness, Assurance, and Empathy. A qualitative approach, specifically a case study, was employed for data collection involving in-depth interviews with cooperative members and direct observation of the service process. Qualitative data analysis employed thematic coding to identify key patterns and insights. The results indicate that each service quality element significantly influences members’ satisfaction. Comfortable physical facilities, reliable services, high responsiveness, transaction security assurance, and empathy in member interactions play crucial roles in fostering member trust and loyalty. Despite the study's focus on a single cooperative, the findings suggest that improvements in facility quality, service reliability, staff responsiveness, transaction transparency, and empathy are essential for strengthening member relationships and enhancing satisfaction. The study also acknowledges limitations such as the focus on a single cooperative, which may limit the generalizability of the results. This study contributes to improving service management in savings and loan cooperatives and provides insights for enhancing their competitiveness in supporting members' welfare and local economies.